2017
DOI: 10.1002/eap.1439
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem carbon density and allocation across a chronosequence of longleaf pine forests

Abstract: Forests can partially offset greenhouse gas emissions and contribute to climate change mitigation, mainly through increases in live biomass. We quantified carbon (C) density in 20 managed longleaf pine (Pinus palustris Mill.) forests ranging in age from 5 to 118 years located across the southeastern United States and estimated above- and belowground C trajectories. Ecosystem C stock (all pools including soil C) and aboveground live tree C increased nonlinearly with stand age and the modeled asymptotic maxima w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 86 publications
2
34
0
Order By: Relevance
“…Interestingly, the model S-17 showed a tendency of overestimating on about 11% all biomass components. Graphical analysis of the actual biomass and that predicted by the equations reported by Baldwin and Saucier [8] (BS-83) and Samuelson et al [19] (S-17), and new equation systems developed in this study indicate that the new equation systems predicted all biomass components on the larger dataset with great precision and accuracy. In Figure 5 we show the results for model system II and VI.…”
Section: Comparison Against Published Equationsmentioning
confidence: 66%
See 4 more Smart Citations
“…Interestingly, the model S-17 showed a tendency of overestimating on about 11% all biomass components. Graphical analysis of the actual biomass and that predicted by the equations reported by Baldwin and Saucier [8] (BS-83) and Samuelson et al [19] (S-17), and new equation systems developed in this study indicate that the new equation systems predicted all biomass components on the larger dataset with great precision and accuracy. In Figure 5 we show the results for model system II and VI.…”
Section: Comparison Against Published Equationsmentioning
confidence: 66%
“…All previously reported, biomass functions for longleaf pine trees rely on DBH only [7,15,19] or DBH and HT [8,9,[15][16][17]19]. When compared with our model system VI, the functions of Baldwin and Saucier [8] and Samuelson et al [19] showed a tendency to estimate biased results.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations